The Controlled Disorder as a USA Transitional Strategy toward Multipolarity - Admir Mulaosmanovic (Journal of Balkan Studies, 2025)
This paper attempts to show the deliberate and systematic actions of the world superpower (USA) in creating a state of controlled chaos. The reason for such an approach lies in the inevitable change in global relations in which the superpower must define its new position and prepare for the near future in which it no longer has a dominant role. This discourse can be used to analyze the reasons for the war in Ukraine, as well as the reasons for the rise in tensions on the great dividing line between East and West. Considering that the established global order is slowly disappearing, and the emerging new multipolar world is increasingly showing signs of strength and vitality, all this opens the door to a general rethinking of future relations. The already disavowed international law and unclear international order are a factor in increasing insecurity throughout the world, while the double standards that have become a basic feature of the Western democracies speak of the serious problems that global politics has fallen into. Additionally, American militarism intertwined with concept of inalienable rights hardly works as universal value anymore. “America first”, Trump’s slogan, can and should be understood in this sense as a return to the isolationist policy, but also to exploit all the opportunities that brings the benefits to US, and not as a necessary call for remaining in the position of a superpower.